How Does Gamification Improve Purchase Intention? Through the Lens of Perceived Brand Coolness and Time Poverty - Yingchuan Liao; Fei Zhou; Youcheng Chen; Yenchun Jim Wu (Behavioral Sciences)
Gamification has been extensively employed in marketing practices to meet the diverse needs of consumers. Previous research suggests that gamification marketing plays a pivotal role in influencing customer purchase intention. However, the precise mechanism through which gamification marketing impacts purchase intention requires further investigation. Drawing on the self-determination theory (SDT), this study explores the relationship between gamification marketing and purchase intention, with customers’ perceived brand coolness as a mediating variable and time poverty as a moderating variable. Using data collected from 184 participants in the experiment, our research demonstrates that, in comparison to non-gamification marketing, gamification marketing significantly influences purchase intention. Furthermore, perceived brand coolness emerges as a mediating factor in this relationship, providing new insights into the gamification mechanism. Customers who are in low time poverty exert more perceived brand coolness and purchase intentions compared with high time poverty in the context of gamification marketing. This study expands the research of gamification by introducing perceived brand coolness to the relationship between gamification marketing and purchase intention. It also contributes to the study of time poverty under the context of gamification marketing.